2020
DOI: 10.31292/jb.v6i1.420
|View full text |Cite
|
Sign up to set email alerts
|

Perspektif Pemikiran Hukum Barat dalam Penemuan Hukum Adat oleh Hakim: Studi Kasus Putusan Sengketa Tanah Adat di Pengadilan Negeri Muara Teweh, Padang, Makale, dan Painan

Abstract: Adat law as empirical knowledge found by judges through western legal thought grows to be normative knowledge. This research tried to prove the hypothesis that judges used positivist legal reasoning in finding adat law applicable in specific cases. This study, written in the form of a legal descriptive research with socio-legal approach, aims to identify and analyze the legal reasoning used by judges to find applicable adat law. This research proves that the judges applied western legal thought to find appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Pendekatan positivistik terhadap kajian hukum adat menjelaskan hukum adat sebagai jurisprudence atau sistem hukum yang menempatkan asas dalam kedudukan tertinggi karena bersifat abstrak; sehingga dapat berlaku pada berbagai tempat dan waktu (Koesnoe, 1979;Pradhani, 2020;Simarmata, 2018). Ajaran hukum adat sebagai jurisprudence telah diajarkan sejak tahun 1909 di Rechtsshool; pada tahun 1924 di Rechtshogeschool; dan di tahun 1921 pada Fakultas Ilmu Hukum dan Sastra Universitas Leiden (Djalins, 2013).…”
Section: A Pendahuluanunclassified
“…Pendekatan positivistik terhadap kajian hukum adat menjelaskan hukum adat sebagai jurisprudence atau sistem hukum yang menempatkan asas dalam kedudukan tertinggi karena bersifat abstrak; sehingga dapat berlaku pada berbagai tempat dan waktu (Koesnoe, 1979;Pradhani, 2020;Simarmata, 2018). Ajaran hukum adat sebagai jurisprudence telah diajarkan sejak tahun 1909 di Rechtsshool; pada tahun 1924 di Rechtshogeschool; dan di tahun 1921 pada Fakultas Ilmu Hukum dan Sastra Universitas Leiden (Djalins, 2013).…”
Section: A Pendahuluanunclassified
“…agree with (Sally Falk Moore, 1978), A semi-autonomous social area is defined and constrained not by its organization, but by the characteristics of the process, the fact that within that area it can create laws (rules) and compel or encourage obedience within that area. (Pradhani, 2020), State court decisions recognize and sometimes amend customary law provisions in concrete cases. (Simarmata, 2019), Indigenous people's rights are recognized in various laws and regulations at various levels of government and also in court decisions.…”
Section: Is a Disclaimer Of Indigenous Confessions Ethical?mentioning
confidence: 99%
“…Utama & Aristya (2015) found that the practice of civil justice accommodates the principles of adat law in the dispute resolution process, such as the principle of light in deciding cases of gender reassignment. Furthermore, research conducted by Pradhani (2020) reported that judges use the perspective of western legal thought in making discoveries of adat law based on jurisprudence, doctrine, and the concept of adat law to measure the validity of a legal action. Then, a study conducted by Hakim & Pradhani (2021) regarding the application of a formalistic approach in finding adat law by judges in disputes over Customary Land Certificates (Surat Keterangan Tanah Adat/SKTA) in Central Kalimantan showed that adat law studies can no longer be separated from state law order, because judges in the court room makes discoveries of adat law through statutory regulations.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach distances the development of adat law from its empirical reality because judges focus on finding compatibility of cases with existing concepts, doctrines and jurisprudence (Pradhani, 2020;Hakim & Pradhani, 2021). Another court decision study conducted by Sari, et.…”
Section: Introductionmentioning
confidence: 99%